Effects of different drugs in combination with PKP/PVP on postoperative pain in patients with osteoporotic compression fractures: a network meta-analysis - Bai, Yiguang; Chen, Qiaoling; Wang, RouMei; Huang, Rui (Frontiers in Surgery, 2024)
Objective: This study aimsaimedwas designed to discussevaluate the postoperative pain effect and clinical efficacy of different drugs combined with PKP or PVP inforin treating osteoporotic vertebral compression fractures (OVCFOVCFs) through a systematic review and network meta-analysis. Methods: We searched five electronic databases, includingnamely, MEDLINE (PubmedPubMed), EMBASE, Web of Science, Google Scholar, and the Cochrane Central Register of Controlled Trials online until, for the treatment of OVCFs through March 2023, about with keywords; zoledronic acid (ZOL),; and teriparatide (TPTD or PTH 1-34),; and calcitonin (CT) combined with PKP/PVP in the treatment of OVCF. Visual Analog Scale. The visual analog scale (VAS) and Oswestry Disability Index (ODI) were the primary outcomes of the network meta-analysis, and the secondary outcome was the diagnostic marker bone mineral density (BMD). Results: Eighteen studies involving 2374 2,374 patients were included in this study. The network meta-analysis results showedrevealed that, in terms of reducing VAS scores, compared with PVP surgery alone, the treatment plan of PVP combined with TPTD iswas most likely to be the treatment associated with the bestgreatest pain relief [MD=-4.99, 95% CI=(-7.45, -2.52)][MD=-5.40, 95%CI=95% CI=(-8.23, -2.56)]. In terms of reducing the ODI dysfunction score, compared with PKP combined with CalPKP alone, PKP combined with ZOL hashad the highest probability of being the best treatment option for reducing the ODI dysfunction score [MD=-9.11, 95% CI=(-14.27, -3.95)][MD=-9.10, 95%CI=95% CI=(-14.67,-3.53 )],. inIn terms of protecting against bone density loss, compared with PKP surgery alone, the treatment ofwith PKP combined with ZOL hashad the best effect inon protecting against bone density [MD=0.39, 95%CI=95% CI= (0.13,0.65)]. Conclusions: Based on the network meta-analysis and SUCRA rankings, this study concluded that adding teriparatide has the advantage of reducing VAS pain scores compared with PVP alone and that adding zoledronate is a more effective treatment for reducing ODI disability scores compared with PKP combined with Cal and preserving BMD compared with compared with PKPPKP alone. MoreHowever, additional high-quality studies are needed to verify our findings in the future.